The Future of Education and Labor: A Book Review - Mahboubeh Asadi; Zahra Karimian (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
The impact of technological changes on life and business has been profound, creating new demands for enterprises today. The concept of labor in the modern era necessitates a workforce with new capabilities. Educational institutions address these needs by aligning their programs with labor market demands. As the global economy increasingly relies on knowledge, a growing academic focus has been on universities' roles in regional economies. This trend acknowledges their role as catalysts for economic development and innovation. The current article reviews the book “The Future of Education and Labor,” which explores the multifaceted impacts of technological changes, along with their economic and educational effects. The book posits that as automation and technological advancements transform the labor landscape, educational institutions must adapt to prepare future workers effectively. Each chapter features insights from various experts, offering a comprehensive view of the pertinent issues.